Grundlagen der Semantik: Dritte Ausgabe - Lipavic Oštir, Alja (University of Maribor Press, 2023)
Basics of Sematics: Third Edition. University textbook contains basic concepts from the semantics study field for students of German language. Single chapters can be used in different linguistics courses of and other studies. The textbook presents basic terms and the semantics of language signs related to single parts of speech. Each term is illustrated and accompanied with several tasks and exercises including different languages. The textbook does not want to state one’s position on different theories in semantics; the goals are only to explain basic concepts and give some suggestions for further study. The structure of the textbook follows the language system and brings some case studies (semantics of nouns compared with adjectives, syntax of genitive semantics). Das vorliegende Universitätslehrbuch bringt Inhalte aus den Bereichen der linguistischen Semantik für Studierende der Germanistik. Einzelne Kapitel können auch im Rahmen anderer Fächer der linguistischen wie auch anderer Studienprogramme eingesetzt werden. Das Lehrbuch erläutert relevante Grundbegriffe und die Semantik der Sprachzeichen hinsichtlich einzelner Sprachebenen. Alle Begriffe werden entsprechend illustriert und von Aufgaben begleitet, in denen Beispiele aus verschiedenen Sprachen vorkommen. Das Lehrbuch nimmt keine Stellung zu einzelnen semantischen Theorien, sondern bringt die Grundinformationen wie auch Vorschläge für das weitere Studium. Seine Struktur ist dem Sprachsystem angepasst, das Lehrbuch enthält aber auch einige Fallstudien (Wortsemantik: Substantivs vs. Adjektiv und die semantischen Genitivinterpretationen).